2021
DOI: 10.2147/ccid.s343876
|View full text |Cite
|
Sign up to set email alerts
|

A Case of IgA Vasculitis During Nivolumab Therapy for Renal Cell Carcinoma

Abstract: A 50-year-old Japanese woman presented with a 4-day history of multiple purpura on her extremities and myalgia. She had been receiving nivolumab therapy for stage IV renal cell carcinoma for 18 months. Nivolumab was temporarily discontinued due to liver dysfunction and resumed 3 months before. Biopsy specimen revealed leukocytoclastic vasculitis, and direct immunofluorescence showed deposition of IgA and C3 in the vessel walls of the upper dermis. Based on these findings, a diagnosis of IgA vasculitis was made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…( 5 )]. We excluded two cases, one due to the absence of histologic evidence ( 17 ) and the second because the final diagnostic was postinfectious GN ( 8 ). Nine were case reports and two cases were described by Mamlouk et al.…”
Section: Discussionmentioning
confidence: 99%
“…( 5 )]. We excluded two cases, one due to the absence of histologic evidence ( 17 ) and the second because the final diagnostic was postinfectious GN ( 8 ). Nine were case reports and two cases were described by Mamlouk et al.…”
Section: Discussionmentioning
confidence: 99%
“…Vasculitis is classified into large-, medium-, and small-vessel types depending on blood vessel size [ 116 ], but ICIs can cause any type of vasculitis. In fact, giant cell arteritis (GCA) [ 117 , 118 ], aortitis and large-vessel involvement [ 119 , 120 , 121 ], IgA vasculitis [ 122 , 123 ], granulomatosis with polyangiitis [ 124 , 125 ], eosinophilic granulomatosis with polyangiitis [ 126 ], and cutaneous small-vessel vasculitis [ 127 , 128 ] have been reported after ICI administration. A retrospective pharmacovigilance study evaluated the association between ICIs and cardiovascular adverse events and demonstrated that ICI treatment was associated with a higher risk of vasculitis when compared with the database obtained from individual case safety reports [ 129 ].…”
Section: Rheumatic Iraesmentioning
confidence: 99%
“…Oral prednisolone (0.5 mg/kg) improved the purpura ( Picture 4 ) and there was no worsening of proteinuria or hematuria. IgA vasculitis following immune checkpoint inhibitor administration has rarely been reported ( 1 , 2 ), and not with atezolizumab. IgA vasculitis should be considered in patients receiving immune checkpoint inhibitors who develop symptoms such as purpura or angioedema.…”
mentioning
confidence: 99%